Phylogenomics redefines the evolutionary history of mosquitoes - Mac P. Pierce; Brian M. Worthington; Shaolin Han; Xue-Bing Ni; Yunshi Liao; Marcus H. Shum; Yi Guan; Edward C. Holmes; Tommy T. Lam (Proceedings of the National Academy of Sciences, 2025)
Mosquitoes have a substantial impact on human and animal health, but their deeper evolutionary relationships have been difficult to resolve. We inferred a time-calibrated phylogenetic history of mosquitoes using conserved genome-wide markers from representatives of major lineages. Our analyses revealed that codon bias and positive selection in subfamily Anophelinae contributed to a substantial level of branch attraction bias between Anophelinae and outgroup taxa, which in our view has misled previous phylogenetic analyses of mosquitoes. Accounting for this systematic phylogenetic bias led to a revised view of mosquito evolution, including the nonmonophyly of subfamily Culicinae. Similarly, we dated the origin of mosquitoes to the mid-Cretaceous (~106 Mya) and most extant genera to after the KPg boundary <66 Mya, 100 My younger than previous estimates and coincident with the origin of Plasmodium parasites. Our study provides a foundation for future analyses of the evolution of mosquito-borne disease.